Membangun Karakter Nasionalisme Pada Generasi Milenial Di Era Globalisasi - Margaretha Evi; Abu prabowo (LPPM Universitas Dharma Andalas, 2022)
This study illustrates the importance of Citizenship Education in shaping the character of the younger generation in the era of globalization in an attitude of nationalism. The research method used is the library method, which is obtained by the author from the data of a book, blog, website, and other journals. The conclusion of this study is how to deal with the impact of a globalization that leads to nationalism by providing knowledge about nationalism by the younger generation through education given to schools and universities, so that it can form a mentality among the younger generation, so that the younger generation has good characteristics and a sense of love. homeland to the nation and state.